Children's and parents' opinions on the sport‐related food environment: a systematic review. (31st May 2017) - Smith, M.; Signal, L.; Edwards, R.; Hoek, J.
Summary: Sport is a key setting for interventions to address child obesity given its obesogenic nature. Understanding children's and parents' opinions on the sport‐related food environment is critical in developing effective programmes and policies to improve children's health. This systematic review synthesizes quantitative and qualitative research examining children's and parents' opinions on the sport‐related food environment. During July 2016, a range of electronic databases of academic and grey literature were searched. Thirty‐two publications (11 including children, 17 parents and 4 both) were included for review. The publications were assessed using the Analysis Grid for Environments Linked to Obesity framework to categorize the sport‐related food environment into the physical, sociocultural, economic and political environments. The literature available investigating children's and parents' opinions of the sport‐related food environment suggests that many children and parents consider the environment neither conducive to nor supportive of children's healthy food behaviours or wider health and well‐being. Both groups would likely support actions to change and improve it. This systematic review found that original research specifically investigating children's and parents' perspectives on almost all aspects of the sport‐related food environment is limited. Thus, there is scope for further investigation into this important part of children's food environments.